PERILAKU HEDONISME SISWA DITINJAU DARI POLA ASUH ORANG TUA - Afrizawati (JURNAL AS-SAID, 2023)
Parenting style is very influential on children's behavior, both in attitude and behavior. The existence of hedonism behavior is because parents prefer happiness for their children, without thinking about the consequences. This study aims to determine the effect of parenting style on hedonism behavior in SPMII Lukman Al-Hakim Batam students. The number of subjects in this study amounted to 100 students, using the Cluster Random Sampling technique. The type of research in this study is correlation research, because this study aims to find out whether there is an influence between parenting styles on hedonism behavior in SMPII Lukman Al-Hakim Batam students. The results in this study indicate that there is an influence of parenting style on hedonism behavior in SMPII Lukman Alhakim Batam students, which is equal to 855%, and another 14.5% is influenced by other factors.